2015
DOI: 10.1039/c4nr06066k
|View full text |Cite
|
Sign up to set email alerts
|

Insight into factors affecting the presence, degree, and temporal stability of fluorescence intensification on ZnO nanorod ends

Abstract: We have carried out a combined experimental and simulation study identifying the key physical and optical parameters affecting the presence and degree of fluorescence intensification measured on zinc oxide nanorod (ZnO NR) ends. Previously, we reported on the highly localized, intensified, and prolonged fluorescence signal measured on the NR ends, termed as fluorescence intensification on NR ends (FINE). As a step towards understanding the mechanism of FINE, the present study aims to provide an insight into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…1015 Anisotropically shaped materials can possess unique light-matter interaction phenomena different from those seen in their isotropic counterparts. 16,17 Previous studies have shown that light interacting with anisotropic materials can result in optically distinctive responses depending on the polarization state of the light, angle of the incident light, and geometric orientation of the nanomaterial.…”
Section: Introductionmentioning
confidence: 99%
“…1015 Anisotropically shaped materials can possess unique light-matter interaction phenomena different from those seen in their isotropic counterparts. 16,17 Previous studies have shown that light interacting with anisotropic materials can result in optically distinctive responses depending on the polarization state of the light, angle of the incident light, and geometric orientation of the nanomaterial.…”
Section: Introductionmentioning
confidence: 99%
“…Pure and chemically doped NRs with comparable physical dimensions are systematically characterized for their material-dependent elastic scattering responses upon interactions with visible light. Specifically, we have chosen single NRs of ZnO as well as indium tin oxide (ITO) and zinc tin oxide (ZTO) due to their well-known functional benefits as lasers, 20,21 light emitters, 22–25 waveguides, 26–30 photovoltaics, 31 and biosensors 32,33 . We subsequently elucidate an intriguing scattering response of rotation in the polarization direction of the scattered light from individual NRs.…”
mentioning
confidence: 99%
“…The insight gained from this study can advance our fundamental understanding of the optical behaviors of the technologically useful nanomaterials and, at the same time, promote the development of highly miniaturized, photonic and bio-optical devices utilizing the spatially controllable, optical responses of the individual semiconducting oxide NRs. [16][17][18][19][20][21][22][23][24] In many of these technologically important applications, the fundamental optical properties of 1D SO nanomaterials govern their functional outcomes. Light can produce various optical and optoelectronic responses from the materials and, therefore, light-matter interactions can be engineered to produce desirable optical properties such as spontaneous and stimulated emission, 1,25-29 waveguiding, 1-3 and evanescence field enhancement.…”
mentioning
confidence: 99%
“…One-dimensional (1D) nanomaterials based on semiconducting oxides (SOs) have demonstrated their useful properties in numerous applications of photonics, 1-4 electronics, [5][6][7][8] optoelectronics, 9,10 photovoltaics, [11][12][13][14][15] and chemical/biological sensing. [16][17][18][19][20][21][22][23][24] In many of these technologically important applications, the fundamental optical properties of 1D SO nanomaterials govern their functional outcomes. Light can produce various optical and optoelectronic responses from the materials and, therefore, light-matter interactions can be engineered to produce desirable optical properties such as spontaneous and stimulated emission, 1,25-29 waveguiding, 1-3 and evanescence field enhancement.…”
mentioning
confidence: 99%
See 1 more Smart Citation